2021
DOI: 10.1186/s40462-021-00289-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Far eastern curlew and whimbrel prefer flying low - wind support and good visibility appear only secondary factors in determining migratory flight altitude

Abstract: Following publication of the original article [1], errors were identified in the presentation of some of the reference citations in the Background section (page 2 of the PDF) and the Conclusion section (page 10 of the PDF) due to a typesetting mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Our finding that geese strongly selected low altitudes aligns with previous work showing that migrating birds often select altitude itself over other covariates. Flying at higher altitudes incurs inherent costs such as the energetic expense of climbing, reduced air density (reducing lift) or higher water loss (Galtbalt et al, 2021;Klaassen, 2004). These costs would be affected by body mass and relative wing-loading (Norberg, 1990), and so could be particularly pronounced in geese, though strong altitude selection has also been −2 SD, mean, and +2 SD, as calculated across all available points in the dataset; or two lines for day versus night for the binary daylight covariate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our finding that geese strongly selected low altitudes aligns with previous work showing that migrating birds often select altitude itself over other covariates. Flying at higher altitudes incurs inherent costs such as the energetic expense of climbing, reduced air density (reducing lift) or higher water loss (Galtbalt et al, 2021;Klaassen, 2004). These costs would be affected by body mass and relative wing-loading (Norberg, 1990), and so could be particularly pronounced in geese, though strong altitude selection has also been −2 SD, mean, and +2 SD, as calculated across all available points in the dataset; or two lines for day versus night for the binary daylight covariate.…”
Section: Discussionmentioning
confidence: 99%
“…A similar analysis has previously been applied to altitude selection in a conditional logistic mixed-effects model (Galtbalt et al, 2021), but we used a conditional Poisson mixed-effects model, as Muff et al (2020) found that to be analytically equivalent but better able to handle a large dataset like ours (thousands of locations).…”
Section: Statistical Analysis: Altitude Selectionmentioning
confidence: 93%
See 3 more Smart Citations